2018
DOI: 10.1111/gbi.12311
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide from chemodenitrification: A possible missing link in the Proterozoic greenhouse and the evolution of aerobic respiration

Abstract: The potent greenhouse gas nitrous oxide (N O) may have been an important constituent of Earth's atmosphere during Proterozoic (~2.5-0.5 Ga). Here, we tested the hypothesis that chemodenitrification, the rapid reduction of nitric oxide by ferrous iron, would have enhanced the flux of N O from ferruginous Proterozoic seas. We empirically derived a rate law, d N Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 135 publications
(229 reference statements)
2
44
0
Order By: Relevance
“…Most NO − X reached the surface in the form of HNO, which 10.1029/2018GC008082 in aqueous settings would then undergo dissociation, homologation, and decay reactions, ultimately yielding soluble NO − 2 and NO − 3 and gaseous N 2 O (Mancinelli & McKay, 1988;Summers & Khare, 2007). Stanton et al (2018) have recently demonstrated the reduction of NO to N 2 O in ferrous waters; we may speculate similar chemodenitrification to occur with NO -. It is difficult to calculate the fraction of fixed nitrogen that escapes back to the atmosphere as N 2 O, because the kinetics of these transformations have not been quantified for NO -.…”
Section: Kinetic Steady Statementioning
confidence: 85%
See 3 more Smart Citations
“…Most NO − X reached the surface in the form of HNO, which 10.1029/2018GC008082 in aqueous settings would then undergo dissociation, homologation, and decay reactions, ultimately yielding soluble NO − 2 and NO − 3 and gaseous N 2 O (Mancinelli & McKay, 1988;Summers & Khare, 2007). Stanton et al (2018) have recently demonstrated the reduction of NO to N 2 O in ferrous waters; we may speculate similar chemodenitrification to occur with NO -. It is difficult to calculate the fraction of fixed nitrogen that escapes back to the atmosphere as N 2 O, because the kinetics of these transformations have not been quantified for NO -.…”
Section: Kinetic Steady Statementioning
confidence: 85%
“…Our analysis could be most improved by better characterization of NOX reaction kinetics under prebiotically relevant conditions, especially its reduction by Fe 2+ and Mn 2+ and its reduction by UV in prebiotic natural waters (e.g., the extension of studies like Stanton et al, , to NOX). Studies with higher‐dimensional models could also help determine if there exist areas in the ocean which should have concentrated NOX above the oceanic mean, perhaps to prebiotically relevant levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microbial production of greenhouse gases under ferruginous conditions has led to the suggestion that gases such as CH 4 or N 2 O could have been important in regulating early Earth's climate when solar luminosities were lower (e.g., Kasting, 2005;Stanton et al, 2018). However, biosphere models for oceanic CH 4 emissions during the Archean and Proterozoic eons generally only consider transport of CH 4 by turbulent diffusion (Olson, Reinhard, & Lyons, 2016), which favors efficient oxidation of CH 4 at an oxycline (Oswald, Jegge, et al, 2016a).…”
Section: Methane Emissions From Ancient Ferruginous Oceansmentioning
confidence: 99%